Examining the effectiveness of monetary policy in Asia4: the pre- and post-1997 Asian financial crisis - Rong, Wei Soon; Yi, Xuan Tan; Siok, Kun Sek; Khang, Yi Sim (Penerbit Universiti Kebangsaan Malaysia, 2024)
One of the main changes experienced by Asian countries due to the 1997 Asian financial crisis was the shift in monetary policy to inflation targeting, along with the release from rigid to flexible exchange rate regimes. This study focuses on four main Asian countries (Korea, Thailand, the Philippines, and Indonesia) that experienced such monetary policy changes. The aim is to evaluate the effectiveness of monetary policy in Asia4 before and after the shift in monetary policy. This research also aims to investigate the behaviour of economic variables (output growth and inflation) in reaction to the monetary policy stances between the two regimes. The data ranges from January 1990 to December 1996 (pre-crisis) and July 1999 to December 2019 (post-crisis). With these two sub-periods of data, a structural vector autoregressive (SVAR) model is applied to examine the performance of monetary policy. Generally, most variables are highly determined by their own shocks, indicating low predictability by other variables in two sub-periods and all of Asia4. However, the economic structure changes across these sub-periods. In the pre-crisis, the economic growth of Indonesia, Korea, and the Philippines was mainly determined by inflationary shocks, whereas output or real shocks are more influential in the post-crisis. The opposite condition holds for Thailand. Nevertheless, real and inflationary shocks are the main sources causing economic fluctuations in these four Asian countries. This study recommends that monetary policy be more accommodating and co-implement fiscal policy.